Pendekatan Restorative Justice dalam Perlindungan Hukum Anak sebagai Pelaku Tindak Pidana : Menyeimbangkan Keadilan dan Pembinaan - Uut Rahayuningsih; Anna Nur Hikmah; Siti Nurcahyati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This paper discusses legal protection for children as offenders in the juvenile justice system in Indonesia through a restorative justice approach. The study aims to analyze the effectiveness of this approach and the challenges faced in its implementation. The method used is normative juridical with a legislative and conceptual approach. The research findings indicate that the restorative justice approach offers a more child-friendly resolution mechanism, protects children from social stigma, and focuses on restoring social relationships. However, its implementation is still hindered by a lack of understanding among law enforcement officials, limited resources, and a legal culture that predominantly favors a retributive approach. A synergy among various parties is needed to enhance the effectiveness of legal protection for child offenders.